The method of determining the optimal number of groups in the study of socio-economic phenomena - Shirinov, B.; Salamova, I.; Шірінов, Б. Г.; Саламова, І. І. (Харківський національний автомобільно-дорожній університет, 2024)
It is common knowledge that the separation of socio-economic event units into homogeneous groups by important characteristics is called grouping in statistics. Grouping is one of the most efficient methods of statistical data processing. Grouping is the most important stage in the study of large-scale social phenomena. In the socio-economic study of statistical data and average, relative, etc. it is necessary to use grouping in the calculation of final indicators. Namely, with the help of correct and convenient grouping, the complexity of social life events can be expressed and reflected with statistical quantities. Therefore, the method of grouping together with the method of summative statistical indicators is a tool for the correct understanding of socio economic events and processes. Grouping is a manifestation of implementing analysis and synthesis, and at this time, the following issues are resolved: 1) Determination of socio-economic types; 2) Studying the structure of socio-economic events; 3) Studying the relationship between organized groups. In problem solving with the grouping method, the following forms of grouping are mainly used: typical, structural, analytical. By means of typical grouping, the most important statistical problem is solved: socio-economic types are determined on aggregate units, that is, separate groups qualitatively different from the aggregate are created. When grouping according to this form, the correct determination of the group sign has a special role. Based on the analysis of the content of the studied event, the basis of the grouping (that is, the main feature in the grouping) is determined. Structural groupings reflect the development of constituent parts of socio-economic events and processes or their structure according to one or another characteristic. Analytical groupings are used to study the interrelationships between phenomena and the various signs affecting them. Through such groupings, it is possible to determine the cause and effect factors influencing the development of the studied phenomenon and process. Each of the aggregate units has an individual characteristic in its development. For this reason, the absolute level of the investigated symptom is different. Those units are grouped by variation (varying) from each other according to the level of research characteristics. Such groups are called sequences of numbers. The number of units (volume) or specific weight relative to the total can be given in the series of numbers; a quality indicator that cannot be counted can also group information. According to the author, the correct determination of the optimal number of groups in the statistical study of socio economic phenomena will give more effective results.
Метод визначення оптимальної кількості груп у дослідженні соціально-економічних явищ
Keywords: grouping; number of groups; quantitative and qualitative characteristics; interval; aggregate; optimal number of groups; equal interval; unequal interval; групування; кількість груп; кількісна та якісна характеристика; інтервал; сукупність; оптимальна кількість груп; рівний інтервал; нерівний інтервал; 311.1; 10.30977/ЕТК.2225-2304.2024.43.144